2020
DOI: 10.1016/j.landurbplan.2020.103871
|View full text |Cite
|
Sign up to set email alerts
|

Integrating a landscape connectivity approach into mitigation hierarchy planning by anticipating urban dynamics

Abstract: Urbanization leads to land-use changes and landscape fragmentation, impacting natural habitats and their connectivity. In principle, many local decision-makers are obliged to adopt a mitigation hierarchy whereby development projects must be designed to avoid impacts on biodiversity, reduce, and ultimately compensate for the remaining impacts to reach the goal of no net loss (NNL) of biodiversity. In practice, however, both developers and regulators lack relevant practical tools to support their strategies to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 101 publications
(122 reference statements)
0
12
0
Order By: Relevance
“…In fact, the proposed method was rational and reproducible thanks to the traceability of the data sources and the deterministic choices. For example, the novelty of working with superimposed layers is used to produce landscape suitability maps using modern geographic information systems (GIS) technologies for geodesign purposes [15,16], environmental analysis [17][18][19] and past and recent modelling [20][21][22][23].…”
Section: Design With Naturementioning
confidence: 99%
“…In fact, the proposed method was rational and reproducible thanks to the traceability of the data sources and the deterministic choices. For example, the novelty of working with superimposed layers is used to produce landscape suitability maps using modern geographic information systems (GIS) technologies for geodesign purposes [15,16], environmental analysis [17][18][19] and past and recent modelling [20][21][22][23].…”
Section: Design With Naturementioning
confidence: 99%
“…This could be rewarded in an improved version of the modeling with a bonus added if a polygon contributes to restoring an ecological corridor or if contiguous selected polygons create a path throughout an identified ecological corridor (as illustrated in Figure 7). The potential contribution of offsets to the restoration of landscape-scale ecological processes has been highlighted recently [41,54,64].…”
Section: Wetland Condition Scoring and Its Limitationsmentioning
confidence: 99%
“…Calvet et al [40] and Bigard et al [14] showcased the potential for landscape-level and SEA approaches to offsetting in Montpellier, implying the need to go beyond a case-by-case permittee-led compensation approach. A similar approach was applied to the city of Toulouse by Tarabon et al [41]. In Lyon, Tarabon et al [42] also showed that offsetting could be used to generate an overall increase in interconnected habitats and thus to increase landscape-level carrying capacity.…”
Section: Introductionmentioning
confidence: 99%
“…In the light of recurrent failures in biodiversity offsetting implementation (see Bezombes et al, 2019;May et al, 2017;Weissgerber et al, 2019), there is growing evidence of the benefits of including landscape connectivity into the mitigation hierarchy (Dalang and Hersperger, 2012;Tarabon et al, 2019bTarabon et al, , 2020. A territorial-scale conservation strategy seems to further increase these benefits.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite recent studies which have used spatial prioritization to demonstrate the value of locating biodiversity offsets in different parts of the landscape (e.g., McKenney and Kiesecker, 2010;Moilanen, 2013) and others which have focused on incorporating connectivity (e. g., Tambosi et al, 2014), the territorial organization of biodiversity offsetting and the benefits generated by their localization and pooling are poorly considered in studies, whatever the form chosen by land developers (Scolozzi and Geneletti, 2012). Yet, organizing and pooling offsets are key to improving and reaping biodiversity offsets benefits (Bigard et al, 2020;Tarabon et al, 2020), particularly in agricultural and suburban areas where the pressure of urbanization is relatively strong and where the landscape usually suffers from fragmentation (Haverland and Veech, 2017).…”
Section: Introductionmentioning
confidence: 99%